Development of Interactive Islamic Education E-Module with Canva: Innovating the Teaching of Hajj and Umrah Material at Junior High School Level - Marwah, Marwah; Safitri, Nurul; Astini, Neny; Yusuf, Munir; Amin, Muh. Agil (South Sulawesi Education Development (SSED), 2024)
This research aims to develop an interactive e-module using the Canva application on Hajj and Umrah material in PAI class IX learning. The e-module development method involves design, validation, revision, and trial by experts and learners. The results showed that the e-module received high expert validation and was practically used by teachers and students. The integration of Canva proves its effectiveness in enhancing teacher creativity and learner engagement. This research contributes to PAI's learning innovation, enriches teaching materials, and creates a more interactive learning experience.